PENGARUH PENANAMAN MODAL ASING DAN DOMESTIK SERTA PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI KABUPATEN/KOTA PROVINSI KALIMANTAN SELATAN TAHUN 2011-2015 - Khairunnisa Khairunnisa; Aris Soelistiyo; Hendra Kusuma (Program Studi Ekonomi Pembangunan, 2017)
the purpose of study was to determine the effect of variable foreign and domestic investment, government expenditure for the gross regional domestic product of Regencies/Cities in South Kalimantan Province. The analysis tool used regression panel data, the result obtained determinasi coeficient R^2 for the fixed effect model of 0,95, this showed that the ability of independent variables in explaning the dependent variable of 95%. The result of the research study conclude that foreign and domestic investment, government expenditure was positif and significant impact on the gross regional domestic product with the result of statistics 66,4 more large than F table is 3,15 while the partial test result showed that foreign and domestic investment, government expenditure was a significant and positive effect on the gross regional domestic product.Keywords : Domestic Investment, Foreign Investment, Government Expenditure, Gross Regional Domestic Product